1985
DOI: 10.1111/j.2042-7158.1985.tb04960.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of drug metabolizing enzymes in the liver of rats infested with Fasciola hepatica

Abstract: Adult, male rats were infected with 20 metacercariae of Fasciola hepatica given orally, other rats were left untreated. Five weeks after infestation, some animals received phenobarbitone, 3-methylcholanthrene, beta-naphthoflavone or Arochlor 1254, to induce liver drug metabolizing enzymes. Fascioliasis provoked decreases in aminopyrine N-demethylase, aniline hydroxylase, the mutagenic activity of cyclophosphamide and cytochrome P-450 concentration in untreated or phenobarbitone or Arochlor pretreated rats. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The origin of the speci®c changes found in antioxidant enzymes could be related to dierent factors, such as the speci®city of toxic excretions of adult¯ukes, the in¯ammatory response of the animals to the presence of parasites, or the particular localization of these enzymes in speci®c areas of the hepatic lobules. Speci®c alterations in dierent isoenzymes of cytochrome P-450 have also been reported in both fasciolosis (Elsheikh et al 1992;Galtier et al 1985) and dicroceliosis (Sa nchezCampos et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of the speci®c changes found in antioxidant enzymes could be related to dierent factors, such as the speci®city of toxic excretions of adult¯ukes, the in¯ammatory response of the animals to the presence of parasites, or the particular localization of these enzymes in speci®c areas of the hepatic lobules. Speci®c alterations in dierent isoenzymes of cytochrome P-450 have also been reported in both fasciolosis (Elsheikh et al 1992;Galtier et al 1985) and dicroceliosis (Sa nchezCampos et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, literature on dicroceliosis is scarce, probably due to the complexity of the parasite life cycle and to the observation that it generally does not cause severe pathological manifestations. In rats and lambs infected with F. hepatica, reductions in cytosolic glutathione and perturbations of calcium homeostasis have been reported, indicating the existence of oxidative cell injury (Galtier et al 1985(Galtier et al , 1987. We have recently shown that experimental dicroceliosis induces an impairment of the capacity of the hamster liver for metabolism of drugs and xenobiotics (Sa nchez-Campos et al 1996), but studies assessing oxidative perturbations and antioxidant enzyme status in the course of this parasitosis are lacking.…”
Section: Introductionmentioning
confidence: 99%